INTERAKSI SOSIAL WANITA PENGRAJIN BATIK TERHADAP KELUARGA DI DESA BAKARAN KABUPATEN PATI - Haqiqi, Arghob Khofiyya (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2019)
: Most of the workers of the home industry of Bakaran batik industry are housewives. Most of their husbands work as farmers or other jobs outside of agriculture. Most batik craft workers are more engaged by women because batik requires precision, tenacity and high perseverance. The problems that occur among women workers are that they are less able to divide their time aside from make batik every day, also have to complete household chores cook, sweep, care for the house and care for children, etc. The purpose of this study was to determine the social interactions between women batik craftsmen and their families. The method used is qualitative methods and result obtained by means of field observations, interviews, and literature studies. The results of this study are that social interaction between women batik craftsmen with their families is well and sometimes conflict occur. Women batik craftsmen hold social contacts and communicate well with family members. The form of interaction between batik craftsmen and families is an associative and dissociative interaction. Associative because there is cooperation and agreement with the family to achieve the goal. Dissociative because there is a dispute between women batik craftsmen and families that sometimes occur resulting in conflict.